2014
DOI: 10.5762/kais.2014.15.4.1953
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Ego Resilience and involvement with the Experience of Anxiety and Perceived Stress in Nursing students

Abstract: Yo u n -k y u n gL e e 1 a n dL i -Hy u nKi m 2 * 1 Di v i s i o no fNu r s i n g ,Ki mc h e o nS c i e n c eCo l l e g e 2 Di v i s i o no fNu r s i n g ,Ch u n g n a m Un i v e r s i t y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Individuals with low ego resiliency tend to lack diversity in healthy strategies in coping with life's challenges (28). Researchers found that ego resiliency was negatively related to the level of anxiety and perceived stress (29,30). Cole et al (31) reported that ego resiliency was negatively related to anxiety and depression.…”
Section: Positive Capital and Mental Healthmentioning
confidence: 99%
“…Individuals with low ego resiliency tend to lack diversity in healthy strategies in coping with life's challenges (28). Researchers found that ego resiliency was negatively related to the level of anxiety and perceived stress (29,30). Cole et al (31) reported that ego resiliency was negatively related to anxiety and depression.…”
Section: Positive Capital and Mental Healthmentioning
confidence: 99%
“…양영희 · 김은만 · 유미 등 연구에서 회복탄력성이 높은 학생들은 전공만족도, 실습만족 도, 그리고 임상수행능력이 높았고 [9,10] 의사소통능력이나 문제해결능력이 좋으며 [11], 불안과 스트레스가 낮았다고 보 고하였다 [12]. 이러한 (Table 2).…”
unclassified